2020
DOI: 10.1016/j.ccell.2020.01.007
|View full text |Cite|
|
Sign up to set email alerts
|

CDK4/6 Inhibitors Impair Recovery from Cytotoxic Chemotherapy in Pancreatic Adenocarcinoma

Abstract: Highlights d CDK4/6 inhibitors should be applied after and not before cytotoxic chemotherapy d CDK4/6 inhibitors prevent DNA repair after mitotic poisons and DNA-damaging agents d Inhibiting CDK4/6 results in an RB1-dependent repression of the DNA-repair machinery d CDK4/6 and PARP inhibitors cooperate in preventing tumor cell proliferation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 67 publications
5
78
1
Order By: Relevance
“…Furthermore, combinational inhibition of both CDK4 and CDK6 is expected to have an even greater benefit to the clinical outcomes of PDAC patients [ 52 ]. It has been shown that an approach which uses CDK4/6 inhibitors after taxanes more effectively slows proliferation of PDAC cells [ 53 ]. Since G2M pathway score can accurately assess the cell cycle activity, we cannot help but speculate that the score may be useful as a biomarker for patient selection for CDK4/6 inhibition for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combinational inhibition of both CDK4 and CDK6 is expected to have an even greater benefit to the clinical outcomes of PDAC patients [ 52 ]. It has been shown that an approach which uses CDK4/6 inhibitors after taxanes more effectively slows proliferation of PDAC cells [ 53 ]. Since G2M pathway score can accurately assess the cell cycle activity, we cannot help but speculate that the score may be useful as a biomarker for patient selection for CDK4/6 inhibition for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First studies propose a benefit of chemotherapy and CDK4/6 inhibition depending on the sequential administration. 87…”
Section: Cdk6 In Melanomamentioning
confidence: 99%
“…Due to their cytostatic action, CDK4/6 inhibitors will be ineffective as single agents and, thus, need to be applied as part of combination treatments with targeted compounds such as MTOR inhibitors or as part of a scheduled regimen with classical chemotherapeutics [75]. Classically seen as a driver of cell cycle progression by phosphorylating and inactivating RB1, recent findings point to a much more complex role by coordinating multiple cellular processes ranging from metabolism over DNA integrity to antigen processing and presentation [76][77][78][79][80][81][82][83]. Given this complexity it may not be a surprise that leukaemic fusion proteins do target such central cellular relais station.…”
Section: Therapeutic Targeting Of the Cell Cycle In Amlmentioning
confidence: 99%